Business Strategy For Property Development In Cengkareng Business City Area - Henri Suharlim dan Rina Adi Kristianti (Universitas Tarumanagara, 2019)
The massive growth of real estate development in Jakarta especially in near area Soekarno-Hatta International Airport and rapid growth Indonesia economic condition due to tax amnesty program that held by government , should increase opportunity for the local and international real estate developer company . This business plan will provide the information and basic concept that needed by business strategist or investors in evaluating aspect feasibility and as guidelines and strategic information for next managers who try to develop suitable construction business concept in Cengkareng , Jakarta Barat which is the location itself near with international airport .This business concept aim to become basic concept for the marketers and business strategist in Cengkareng Business City (CBC) to redevelope blank site area into suitable and profitable building product for the investors by providing useful information , calculation , and design concept for next project in CBC . Based on result of businessn plan feasibility study , this business plan is calculated to achieve good results for investment by gaining NPV value of Rp219,556,798,184.16 , by using assumption cost of capital 10% . It also planned to gain IRR value 30 % , it bigger than yearly rate 10% . It shows that the investment for this business plan can exceed the rate of investment that aimed by CBC investors themselves .